(untitled) (Journal of Comparative Social Work, 2007)
Why are institutions of higher education interested in internationalization? The question was asked at a faculty meeting in our university college. A variety of arguments and opinions were expressed. Many “when”, “what”, “how”, “who” and “why” questions were asked. Some arguments were normative and altruistic emphasizing the need of helping to develop countries in improving their educational system, others took a more ideological stand explaining internationalization within a neo-liberal and globalized frame, and some arguments emphasized the importance of a comparative approach to improve the quality of national education.